Description of Work Motivation of The Management of HMJ Islamic Psychology UIN Antasari Banjarmasin During Pandemic - Yulia Wahyu Anggraeni; Selma Jasmine Lubuk; Indah Fatriana; Abdul Jalil; Shanty Komalasari; Ceria Hermina (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2023)
The pandemic has had an impact on system changes in the organization, thus creating its own challenges for the management. To face this challenge, work motivation is needed by each individual who joins the HMJ Islamic Psychology organization to achieve a common goal until the end. The purpose of this study, among others, is to find out a description of the work motivation of administrators who continue to carry out activities during the pandemic. The method used is descriptive qualitative approach and data collection techniques using unstructured interview techniques. The results of the study showed that the work motivation of the HMJ Islamic Psychology board was still in the good category even though they were active during the pandemic.